Absolute quantification of donor‐derived cell‐free DNA as a marker of rejection and graft injury in kidney transplantation: Results from a prospective observational study. Issue 11 (28th May 2019) - Oellerich, Michael; Shipkova, Maria; Asendorf, Thomas; Walson, Philip D.; Schauerte, Verena; Mettenmeyer, Nina; Kabakchiev, Mariana; Hasche, Georg; Gröne, Hermann‐Josef; Friede, Tim; Wieland, Eberhard; Schwenger, Vedat; et al.
Abstract : Donor‐derived cell‐free DNA (dd‐cfDNA) is a noninvasive biomarker for comprehensive monitoring of allograft injury and rejection in kidney transplantation (KTx). dd‐cfDNA quantification of copies/mL plasma (dd‐cfDNA[cp/mL]) was compared to dd‐cfDNA fraction (dd‐cfDNA[%]) at prespecified visits in 189 patients over 1 year post KTx. In patients (N = 15, n = 22 samples) with biopsy‐proven rejection (BPR), median dd‐cfDNA(cp/mL) was 3.3‐fold and median dd‐cfDNA(%) 2.0‐fold higher (82 cp/mL; 0.57%, respectively) than medians in Stable Phase patients (N = 83, n = 408) without rejection (25 cp/mL; 0.29%). Results for acute tubular necrosis (ATN) were not significantly different from those with biopsy‐proven rejection (BPR). dd‐cfDNA identified unnecessary biopsies triggered by a rise in plasma creatinine. Receiver operating characteristic (ROC) analysis showed superior performance ( P = .02) of measuring dd‐cfDNA(cp/mL) (AUC = 0.83) compared to dd‐cfDNA(%) (area under the curve [AUC] = 0.73). Diagnostic odds ratios were 7.31 for dd‐cfDNA(cp/mL), and 6.02 for dd‐cfDNA(%) at thresholds of 52 cp/mL and 0.43%, respectively. Plasma creatinine showed a low correlation ( r = 0.37) with dd‐cfDNA(cp/mL). In a patient subset (N = 24) there was a significantly higher rate of patients with elevated dd‐cfDNA(cp/mL) with lower tacrolimus levels (<8 μg/L) compared to the group with higher tacrolimus concentrations ( P = .0036) suggesting that dd‐cfDNA may detect inadequate immunosuppression resulting in subclinical graft damage. Absolute dd‐cfDNA(cp/mL) allowed for better discrimination than dd‐cfDNA(%) of KTx patients with BPR and is useful to avoid unnecessary biopsies. Abstract : Donor‐derived cell‐free DNA concentrations in combination with fractions measured repeatedly after kidney transplantation allow for clinical laboratory monitoring of graft damage, including rejection, to aid personalized patient care.